Східна і південна межі України з перспективи запорозького козацтва доби Нової Січі - Брехуненко, В. (Чорноморська минувшина, 2023)
Мета статті полягає в дослідженні уявлень запорозького козацтва про південний та східний українські кордони в часи останньої Запорозької Січі. Простежено, що тогочасна запорозька старшина успадкувала переконання запорожців, зафіксовані в джерелах вже в останньому десятилітті XVII ст. Її погляди також виразно перекувалися з «символічною географією» еліти Гетьманщини. Генетично ж комплекс уявлень запорожців своїми коріннями заходить у «ментальні мапи» традиційної української ранньомодерної еліти – князів і шляхти. Доведено, що запорозька верхівка ототожнювала східний та південний кордони Вольностей Війська Запорозького Низового з відповідними межами українського простору. З’ясовано, що оптимальної межею на півдні козаки стабільно вважали узбережжя Чорного моря між гирлом Дніпра і Білгородом, а на сході – річку Дон та північне узбережжя Азовського моря. Просування на Кубань, яке простежується щонайменше з 1730-х рр., призвело до включення до «свого» простору й південно-східного узбережжя Азовського моря до Єйської коси включно. Простежено підходи запорозької старшини до обґрунтування легітимності своїх територіальних претензій. Показано, що запорожці використовували ті ж історичні та правові аргументи, якими послуговувалася еліта Гетьманщини. Відфільтровано алгоритм виборювання козаками своїх просторових інтересів у стосунках з Петербургом та Військом Донським. Розглянуто особливості опанування запорозьким козацтвом простору на півдні та сході. This article aims to explore the perceptions of Zaporizhian Cossacks about the southern and the eastern Ukrainians borders in the times of the last Zaporizhian Sich. The studies have shown that Zaporizhian chief leaders of that time inherited Zaporizhian Cossacks’ beliefs and opinions that were recorded in reference sources as far back as in the last decade of the XVIIth century. Their opinions were also significantly re-shaped with the «symbolic geography», of the Hetmanate top leaders. Genetically, the set of Zaporizhian Cossacks’ beliefs and opinions has its roots in «mental maps» of the traditional Ukrainian early modern elite i.e. princes and nobility (shlyakhta). It has been proven that Zaporizhian leaders identified the southern and the eastern borders of the Domain of the Lower Zaporizhian Host (Viysko Zaporizke Nyzove) with the respective limits of the Ukrainian territorial space. It has been found out that the Cossacks consistently considered the coast of the Black sea between the Dnipro estuary and the city of Bilgorod as the optimal limit in the south, and the river Don and the northern cost of the Azov sea as the optimal limit in the east. Expansion to Kuban observed from the years 1730 at least resulted in inclusion of the south-eastern coast of the Azov sea up to and including Yeysk Spit into the ‘own’ territorial space. The approaches of Zaporizhian leaders as to justification of their territorial claims legitimacy have been observed. It has been shown that Zaporizhzia Cossacks used the very same historical and legal proof-points that had been used by the Hetmanate top leaders. The pattern of lobbying the territorial interests by the Cossacks in relationships with the St. Petersburg and the Don Cossack Host has been checked. Peculiarities of assimilation of the territories by Zaporizhian Cossacks in the south and in the east have been examined.